Students’ Interest in Learning English: A Need Analysis for Teaching Large English Classes - Dinovia Fannil Kher (Lectura : Jurnal Pendidikan, 2022)
In many universities in Indonesia, teaching large English classes is not unusual. It is common to have more than 50 students seated in a class taking an English subject. It is also prevalent that the students are studying different majors, but none of them are English department students. This study aims at obtaining information that will be taken as the base to have a well-designed language program. This study was descriptive research using a survey as the main instrument. A set of questionnaires were distributed to 100 students taking an English subject at the university, aiming at gathering information under three notions; what students believed in learning English, what they expected and how they measured their English ability. The research findings showed that 98.4% of the students believed that English was important due to its dominance in almost every aspect of their life. In addition, 95.2% of the students expected that English class would help them in their speaking since speaking was often said the first way that people took to measure a person’s ability. However, 90% of the students admitted that their English had not improved in any significant way, that they prefer to be taught basic English. Referring to the research findings, it can be concluded that every large English class teacher should be wise to determine the input or the content of the lesson for the students, the process presented and what expected learning outcomes should be highlighted.